The International Handbook of Social Enterprise Law Benefit Corporations and Other Purpose-Driven Companies - Peter, Henry; Vargas Vasserot, Carlos; Alcalde Silva, Jaime; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open-access book brings together international experts who shed new light on the status of social enterprises, benefit corporations and other purpose-driven companies. The respective chapters take a multidisciplinary approach (combining law, philosophy, history, sociology and economics) and provide valuable insights on fostering social entrepreneurship and advancing the common good. In recent years, we have witnessed a significant shift of how business activities are conducted, mainly through the rise of social enterprises. In an effort to target social problems at their roots, social entrepreneurs create organizations that bring transformative social changes by considering, among others, ethical, social, and environmental factors. A variety of social enterprise models are emerging internationally and are proving their vitality and importance. But what does the term (3z(Bsocial enterprise(3y (Bmean? What are its roots? And how does it work in practice within the legal framework of any country? This handbook attempts to answer these questions from a theoretical, historical, and comparative perspective, bringing together 44 contributions written by 71 expert researchers and practitioners in this field. The first part provides an overview of the social enterprise movement, its evolution, and the different forms entities can take to meet global challenges, overcoming the limits of what governments and states can do. The second part focuses on the emergence of benefit corporations and the growing importance of sustainability and societal values, while also analyzing their different legal forms and adaptation to their regulatory environment. In turn, the last part presents the status quo of purpose-driven companies in 36 developed and emerging economies worldwide. This handbook offers food for thought and guidance for everyone interested in this field. It will benefit practitioners and decision-makers involved in social and community organizations, as well as in international development and, more generally speaking, social sciences and economics.s
Foreword -- Introduction -- PART I: The Social Enterprise Movement -- The social enterprise movement and the birth of hybrid organizational forms as policy response to the growing demand for firm altruism -- Social enterprises in the European Union: gradual recognition of their importance and models of legal regulation -- The Governance Patterns of Social Enterprises Two Proposals to Reconcile the US and European Approaches -- Social Enterprises and Tax: Living Apart Together? -- Corporate Purpose : How the Board of Directors can Achieve an Inclusive Corporate Governance Regime -- Social Enterprise: Conceptual Debates and Approaches -- Models and Trends of Social Enterprise Regulation in the European Union -- Social enterprises in the social cooperative form -- How social entrepreneurs create systemic change A comparative analysis of for-profit and non- profit models -- PART II: Benefit Corporations and B Corp Certification -- Benefit Corporations: Trends and Perspectives -- Behavioral Perspectiveson B Corps -- B Lab and the process of certificating B Corps -- Introduction to the law of Benefit Corporations and other public purpose-driven companies -- Benefit Corporations and the Common Law Tradition -- Viability of non-recognized benefit corporations -- Real-World Lessons on Stakeholder Capitalism: How B Lab & B Corp movement catalyze change in society -- PART III: Purpose-Driven Companies: An International Overview -- Social Enterprises and Benefit Corporations in Argentina -- The Failed Attempt to Enact Benefit Company Legislation in Australia and the Rise of B Corps -- Social Enterprises and Benefit Corporations in Brazil: Projects for Corporate Qualification and Capital Market Regulation -- The suitability of Belgian Law to B-Corp -- B Corps, Benefit Corporations and socially oriented enterprises in Canada -- Purpose-driven companies and the projected legal system for benefit and collective interest companies in Chile -- Social Enterprises and Benefit Corporations in China -- Social Enterprises and Benefit Corporations in Colombia -- Social Enterprises and B-Corps in Ecuador -- The suitability of French Law to B-Corp -- Social Purposes in German Corporate Law and Benefit Corporations in Germany -- Social Enterprises and Certified B Corporations in Hong Kong: Development, Key Lessons Learnt and Ways Forward -- B-Corps in India: A Sustainable Business Model -- Social Enterprises and Benefit Corporations in Italy -- Corporations with Social Aims in the Japanese Legal System -- The suitability of Luxembourgish Law to B-Corp -- Certified B Corps in Mexico -- Benefit Corporations in the Peruvian legal ecosystem -- Social Enterprises and Benefit Corporations in Portugal -- Finding space for the B-Corporation within the South African legal landscape -- Social Enterprises and Benefit Corporations in South-Korea -- Social Enterprises and Benefit Corporations in Spain -- Social Enterprises and Benefit Corporations in Switzerland -- Social Enterprises in the Netherlands: Towards more institutional diversity? -- Social Enterprises, Benefit Corporations and Community Interest Companies: The UK Landscape -- Social Enterprises and Benefit Corporations in the United States -- Innovation in Uruguayan Business Law: The (3z(BBenefit and Collective Interest Companies and Trusts(3y (B-- Legal regulation of social enterprises in other European countries.s
Keywords: Private international law; Conflict of laws; International law; Comparative law; Commercial law; Business ethics; Welfare economics; Private International Law, International and Foreign Law, Comparative Law; Business Law; Business Ethics; Social Economy